Review of the environmental and health risks of hydraulic fracturing fluids - Sara Makki; Elsa Maalouf; Alissar Yehya (Heliyon)
The composition of hydraulic fracturing (HF) fluid poses risks to human health and the environment by impacting drinking water sources. Fracturing fluid recovery rate is highly variable, and the fact that a high percentage of the injected HF fluid is not produced back to the surface in some areas raises questions about its fate and possible migration into aquifers. In this paper, the composition of the HF fluid and related toxicity are described, along with insights about the environmental impact linked with HF fluid, synthesized spill data, main factors affecting the flow-back ratio, and induced seismicity related to HF activities. The environmental and health hazards posed by HF fluid are concerning due to the high concentration of toxic chemicals, the limited data on toxicity, the high probability of spills, and the reported cases of aquifer contamination. Furthermore, low load recovery values (10%–50 %) suggest that a significant volume of fracturing fluids may remain in the subsurface, thereby potentially increasing the likelihood of fluid migration towards drinking water sources under certain conditions. Hence, the fate of HF fluid is explained by establishing correlations between fluid flow (i.e., flow-back and migration to the subsurface) and different operation and formation parameters. For example, a negative correlation was detected between HF fluid recovery and shut-in period, fracture network complexity, and induced seismicity, while a positive correlation was observed between HF fluid migration speed and permeable pathways. Moreover, it is shown that the main handicap in assessing related risks is the scarcity of disclosure and monitoring data. Consequently, future work must focus on imposing strict disclosure and incident-reporting regulations, and more publications should be dedicated to inspecting the composition and impact of HF fluid.